2017
DOI: 10.1007/s00464-017-5454-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesh fixation methods and chronic pain after transabdominal preperitoneal (TAPP) inguinal hernia surgery: a comparison between fibrin sealant and tacks

Abstract: Mesh fixation technique did not affect long-term persistent pain. A large number of patients reported persistent pain regardless of mesh fixation technique, which emphasizes the need for preoperative information. Preoperative pain was a risk factor for persistent pain, whereas male gender was protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 24 publications
0
23
0
1
Order By: Relevance
“…Unlike the aforementioned meta-analyses, on comparing tack mesh fixation vs. non-fixation Sajid et al [ 15 ] did not find any difference in the chronic pain rates. Likewise, a registry-based Danish study did not find any difference in chronic pain rates after TAPP operation on comparing mesh fixation with fibrin glue vs. tacks [ 24 ]. In our study, the influence of penetrating tacks on chronic pain was only confirmed for pain on exertion on comparing non-fixation vs. tack fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the aforementioned meta-analyses, on comparing tack mesh fixation vs. non-fixation Sajid et al [ 15 ] did not find any difference in the chronic pain rates. Likewise, a registry-based Danish study did not find any difference in chronic pain rates after TAPP operation on comparing mesh fixation with fibrin glue vs. tacks [ 24 ]. In our study, the influence of penetrating tacks on chronic pain was only confirmed for pain on exertion on comparing non-fixation vs. tack fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Another registry-based study from the Danish Hernia Database also found no difference in chronic pain after mesh fixation with fibrin glue vs. tacks in TAPP inguinal hernia repair [ 24 ].…”
mentioning
confidence: 99%
“…The use of alloplastic materials has become the standard procedure in inguinal hernia surgery [1][2][3][4][5][6]. Hernia surgery is one of the most common visceral operations and thus of great medical and economic importance.…”
Section: Introductionmentioning
confidence: 99%
“…Hernia surgery is one of the most common visceral operations and thus of great medical and economic importance. Many publications have shown that there are advantages in the early postoperative outcome and lower recurrence rate when using techniques with mesh implantation compared with mesh-free inguinal hernia repair [1][2][3][4][5][6]. Therefore, inguinal hernia repair with mesh has become the standard in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation